Collision of fundamental rights: weighing and balancing the spectrum of the dignity of the human person (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This paper aims to reinforce that solution about real cases involving collision of fundamental rights by balancing and weighing, grounded on theory of principles, performs also, and ever, under spectrum of human dignity. Therefore, from a real life case under the Court (“catholic saints under pop characters”), ventures on discussing a methodology for decision making process, counting with a final test of compatibility and adherence to human dignity, in order that decisions to be taken avoid at maximum exhausting for complete the nuclear part of each of those involved fundamental rights, which is precisely the human dignity and its promotion from them.
Keywords: fundamental rights; principles; human dignity; balancing; weighing; teste of compatibility; adherence